2016
DOI: 10.1007/s11661-016-3621-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanisms of Alloying Element Nitrides in Recrystallized and Deformed Ferritic Fe-Cr-Al Alloy

Abstract: The effect of the initial microstructure (recrystallized or cold-rolled) on the nitride precipitation process upon gaseous nitriding of ternary Fe-4.3 at. pct Cr-8.1 at. pct Al alloy was investigated at 723 K (450°C) employing X-ray diffraction (XRD) analyses, transmission electron microscopy (TEM), atom probe tomography (APT), and electron probe microanalysis (EPMA). In recrystallized Fe-Cr-Al specimens, one type of nitride develops: ternary, cubic, NaCl-type mixed Cr 1Àx Al x N. In cold-rolled Fe-Cr-Al speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…This minimal difference may be due to either the above mentioned equilibrium dissolved nitrogen, plus (a very minimal amount of) excess nitrogen. Hence, the stoichiometry of the vanadium nitride is clearly given by VN: no Fe is contained in the nitrides as likely erroneously indicated by APT (and atom probe field ion microscopy) analysis, 19,4953,56 in agreement with results from earlier work in Hosmani 45 , where ‘less perfect’ denitriding in pure H 2 was performed. On the basis of the results presented here, the method proposed, applying a low nitriding potential during denitriding, was very recently also successfully applied by the present authors for nitrides with a very low stability: Mo-containing nitrides in nitrided Fe–1 at.-%Cr–1 at.-%Mo alloy.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…This minimal difference may be due to either the above mentioned equilibrium dissolved nitrogen, plus (a very minimal amount of) excess nitrogen. Hence, the stoichiometry of the vanadium nitride is clearly given by VN: no Fe is contained in the nitrides as likely erroneously indicated by APT (and atom probe field ion microscopy) analysis, 19,4953,56 in agreement with results from earlier work in Hosmani 45 , where ‘less perfect’ denitriding in pure H 2 was performed. On the basis of the results presented here, the method proposed, applying a low nitriding potential during denitriding, was very recently also successfully applied by the present authors for nitrides with a very low stability: Mo-containing nitrides in nitrided Fe–1 at.-%Cr–1 at.-%Mo alloy.…”
Section: Resultssupporting
confidence: 86%
“…Direct determination of the nitrogen content of individual nitride precipitates by local elemental analysis employing either (scanning) transmission electron microscopy in combination with energy dispersive X-ray spectroscopy or electron energy loss spectroscopy, or atom probe (tomography) is difficult due to the very small size of the finely distributed, nano-sized alloying element nitrides. Although these techniques allow establishment of the whether or not occurring co-precipitation of two (metallic) alloying elements in the form of ternary (Me 1 ) x (Me 2 ) 1-x N y nitrides in ternary Fe-Me 1 -Me 2 alloys, [48][49][50][51] quantitative composition analysis by these methods is imprecise (see Wagner and Brenner, 19 Miyamoto et al, 49 Steiner et al, 50 Akhlaghi et al, 51 Jessner et al, 52 Gault et al, 53 Joy et al, 54 Ginter et al, 55 Brenner and Goodman 56 ): for example, considerable amounts of Fe are seemingly (at least to a large extent) detected by atom probe tomography (APT) to be present inside the precipitates. 50,51 The respective amounts of strongly bonded nitrogen, equilibrium dissolved nitrogen and the two types of excess nitrogen (dissolved and adsorbed/segregated) can be determined experimentally by recording so-called nitrogen-absorption isotherms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffusion zone consists of interstitial nitrogen dissolved in the Feα lattice and Fe alloy carbonitrides [39][40][41]. It has been shown that the high surface hardness obtained as a result of nitriding results from the precipitation of fine-grained alloy carbonitrides [42][43][44]. The latter is a consequence of the presence of strongly nitride-forming elements in the steel substrate, such as Al, Cr, Mo, Ti, Mn, Si, and V [43][44][45].…”
Section: Introductionmentioning
confidence: 99%